Improving Fine Motor Skills with Finger Painting in Early Childhood - Riri Octavianti; Mulia Marita Lasutri Tama (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
UNICEF in 2015, there was a high data on the incidence of growth and development disorders in children, especially motor development disorders, there were (27.5%) or 3 million children who experienced disorders. National data according to the Indonesian Ministry of Health that in 2014, 13% to 18% of children in Indonesia experienced growth and development disorders. Finger Painting can develop children's expression through the medium of painting with hand movements, develop fantasy, imagination, and children's creations, train the muscles of the hands and fingers, coordination of muscles and eyes, train creativity in combining colors. Finger Painting is an activity of making drawings that is done by scratching the color dough (paint) directly with the fingers of the hand freely on paper or medial drawings. This study aims to determine the Effect of Finger Painting for Improving Fine Motor Skills in Early Childhood at Tk Al-Kahfi Palembang. With the subject of 10 children aged 5 years. This study used one group pretest and posttest design. This study used a non-parametric statistical test, namely the Wilcoxon test. From the results of the study, differences were obtained between pretest scores and posttest scores. There are also behavioral changes in children in fine motor skills such as grasping objects, writing, and folding paper. Therefore, from the results of the study, it can be concluded that there is an influence in the use of the Finger-Painting technique on improving fine motor skills in children in Al-Kahfi Kindergarten Palembang.UNICEF pada tahun 2015, terdapat data yang cukup tinggi pada angka terjadinya gangguan pertumbuhan dan perkembangan pada anak khususnya gangguan perkembangan motorik terdapat (27,5%) atau 3 juta anak yang mengalami gangguan. Data nasional menurut Kementerian Kesehatan Indonesia bahwa pada tahun 2014, 13% hingga 18% anak di Indonesia mengalami kelainan pertumbuhan dan perkembangan. Finger Painting dapat mengembangkan ekspresi anak melalui media lukis dengan gerakan tangan, mengembangkan fantasi, imajinasi dan kreasi anak, melatih otot-otot tangan dan jari, koordinasi otot dan mata, melatih kreativitas mengombinasikan warna. Finger Painting adalah kegiatan membuat gambar yang dilakukan dengan cara menggoreskan adonan warna (cat) secara langsung dengan jari tangan secara bebas pada kertas atau medial gambar. Penelitian ini bertujuan untuk mengetahui Pengaruh Finger Painting Untuk Peningkatan Kemampuan Motorik Halus Pada Anak Usia Dini Di TK Al-Kahfi Palembang. Dengan subjek 10 orang anak berusia 5 tahun. Penelitian ini menggunakan one group pretest and posttest design. penelitian ini menggunakan uji statistik non parametrik yaitu uji Wilcoxon. Dari hasil penelitian didapatkan perbedaan antara skor pretest dan skor posttest. Juga terdapat perubahan perilaku pada anak dalam kemampuan motorik halus seperti menggenggam benda, menulis dan melipat kertas. Maka dari hasil penelitian dapat disimpulkan bahwa terdapat pengaruh dalam penggunaan teknik Finger Painting terhadap peningkatan kemampuan motorik halus pada anak di TK Al-Kahfi Palembang.